Analysis of SNP-SNP interactions and bone quantitative ultrasound parameter in early adulthood - María Correa-Rodríguez; Sebastien Viatte; Jonathan Massey; Jacqueline Schmidt-RioValle; Blanca Rueda-Medina; Gisela Orozco (BMC, 2017)
Abstract Background Osteoporosis individual susceptibility is determined by the interaction of multiple genetic variants and environmental factors. The aim of this study was to conduct SNP-SNP interaction analyses in candidate genes influencing heel quantitative ultrasound (QUS) parameter in early adulthood to identify novel insights into the mechanism of disease. Methods The study population included 575 healthy subjects (mean age 20.41; SD 2.36). To assess bone mass QUS was performed to determine Broadband ultrasound attenuation (BUA, dB/MHz). A total of 32 SNPs mapping to loci that have been characterized as genetic markers for QUS and/or BMD parameters were selected as genetic markers in this study. The association of all possible SNP pairs with QUS was assessed by linear regression and a SNP-SNP interaction was defined as a significant departure from additive effects. Results The pairwise SNP-SNP analysis showed multiple interactions. The interaction comprising SNPs rs9340799 and rs3736228 that map in the ESR1 and LRP5 genes respectively, revealed the lowest p value after adjusting for confounding factors (p-value = 0.001, β (95% CI) = 14.289 (5.548, 23.029). In addition, our model reported others such as TMEM135-WNT16 (p = 0.007, β(95%CI) = 9.101 (2.498, 15.704), ESR1-DKK1 (p = 0.012, β(95%CI) = 13.641 (2.959, 24.322) or OPG-LRP5 (p = 0.012, β(95%CI) = 8.724 (1.936, 15.512). However, none of the detected interactions remain significant considering the Bonferroni significance threshold for multiple testing (p<0.0001). Conclusion Our analysis of SNP-SNP interaction in candidate genes of QUS in Caucasian young adults reveal several interactions, especially between ESR1 and LRP5 genes, that did not reach statistical significance. Although our results do not support a relevant genetic contribution of SNP-SNP epistatic interactions to QUS in young adults, further studies in larger independent populations would be necessary to support these preliminary findings.